2023
DOI: 10.1093/jacamr/dlad055
|View full text |Cite
|
Sign up to set email alerts
|

Assessing clinical cure of empirical piperacillin/tazobactam for ESBL urinary tract infections (ACCEPT—UTI)

Abstract: Background Data are limited regarding use of piperacillin/tazobactam for ESBL urinary tract infections (UTIs). The objective of this study was to compare clinical outcomes of patients treated empirically with piperacillin/tazobactam versus carbapenems for ESBL UTIs. Methods This retrospective, observational, propensity score-matched study evaluated adults with an ESBL on urine culture. Patients who had UTI symptoms or leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Gbacteria had very low sensitivity to β-lactam antibiotics (ampicillin, piperacillin), but showed good sensitivity to β-lactam antibiotics combined with βlactamase inhibitors-sulbactam/tazobactam The combination showed good sensitivity and signi cantly reduced resistance. Moreover, it has been shown that the success rate of piperacillin/tazobactam in the treatment of urinary tract infections with ESBL(+) infections was not signi cantly different compared to carbapenems [13] . The current study found higher susceptibility to cefotetan, cefepime and ceftazidime among the three generations of cephalosporins but lower susceptibility to ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%
“…Gbacteria had very low sensitivity to β-lactam antibiotics (ampicillin, piperacillin), but showed good sensitivity to β-lactam antibiotics combined with βlactamase inhibitors-sulbactam/tazobactam The combination showed good sensitivity and signi cantly reduced resistance. Moreover, it has been shown that the success rate of piperacillin/tazobactam in the treatment of urinary tract infections with ESBL(+) infections was not signi cantly different compared to carbapenems [13] . The current study found higher susceptibility to cefotetan, cefepime and ceftazidime among the three generations of cephalosporins but lower susceptibility to ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the worrisome ever-growing increase in carbapenem-resistant Gram-negative infections promoted by the selective pressure deriving from extensive carbapenem use [ 16 , 17 ] may call into question the potential role that carbapenem-sparing strategies based on piperacillin–tazobactam could have in some non-severe clinical scenarios of ESBL-producing Enterobacterales infections [ 10 ]. In this latter regard, several well-designed observational studies have shown that no significant difference exists in terms of the mortality rate between piperacillin–tazobactam and carbapenems in the treatment of secondary BSIs caused by ESBL-producing Enterobacterales [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Additionally, the use of piperacillin–tazobactam compared with that of carbapenems was associated with a lower occurrence of colonization and/or infection caused by multidrug-resistant (MDR) or carbapenem-resistant Gram-negative pathogens.…”
Section: Introductionmentioning
confidence: 99%